The impact of speculum uses on the incidence of blepharoptosis in patients undergoing phacoemulsification surgery: A prospective analysis - Savithiri Palanivel; Rajagopalan Jayagayathri; Dayakar Yadalla (Indian Journal of Ophthalmology)
Purpose: The primary objective of this study was to investigate the possible role and assess the potential relationship of speculum use during phacoemulsification surgery in the occurrence of blepharoptosis. Methods: Our study is a prospective observational design to analyze patients who underwent phacoemulsification surgery under topical anesthesia between October 2017 and May 2018 at a tertiary eye hospital in South India. All patients had their Margin Reflex Distance 1 (MRD1), levator palpebrae superioris (LPS) function, and lid crease distance (LCD) measured before and after surgery on day one, one month, three months, and six months to evaluate the extent of ptosis at each time point that was recorded clinically and photographic documentation for accurate evaluation. Results: Out of the 221 patients who participated in the study, a total of 250 eyes were examined. On postoperative day one, 34 patients (15.8% with a rigid speculum and 11.4% with a non-rigid speculum) developed ptosis. At the one-month follow-up, ptosis persisted in four patients, with one patient having undergone surgery using a rigid speculum and the rest of three patients with a non-rigid speculum. However, further follow-ups at three and six months revealed a complete resolution of ptosis in all cases, indicating that the ptosis was transient and resolved spontaneously. Conclusion: Speculum use cannot be considered as the sole causative factor for postoperative ptosis, as a multitude of other modifiable factors, such as superior rectus bridle suturing, anesthetic approach, prolonged patching, and duration of surgery, may have an additive effect alongside speculum used in the development of postoperative ptosis.